Design of circularly polarized end-fire antenna - Wu, Linying (2014)
An circularly polarized endfire antenna is designed by using knowledge of dielectric resonator antenna (DRA). The excitation mode used is 〖TM〗_01δ. It effectively offers a bandwidth of ~38.3% for the return loss below -10dB where the frequency range is from 2.7 to 3.85 GHz with the center frequency 3GHz. This design is applicable to distant comummunication. Furthermore, it also provides a flexibility in signal transmission diection. The simulation is performed on HFSS.